Chapel next to the Vetal Dev Temple - Mumbai Archive Project Team (Jio Institute, 2024)
Christian Kolis pray at the chapel, constructed in 2005 near the tip of the peninsula, next to the Vetal Dev Temple. They celebrate mass at the chapel to commemorate the start of the fishing season.